Steps in an Orapuh Review - Adamu, V. E. (Orapuh Protocols, 2023)
An Orapuh Review is a standalone survey of current scholarly sources on a specific oral and/or public health topic to provide an (updated) overview of knowledge in that area. Orapuh Reviews are published by the journal, Orapuh Literature Reviews (oraprev.orapuh.org). An Orapuh Review involves 17 steps from conception to the final published product. The 17 steps are grouped into 3 major stages: preparation, review, and production.